Design and validation of an agent-based driving simulator - Gregoriades, Andreas; Pampaka, Maria; Michail, Harris; Viugova, Maria (My University, 2018)
The paper describes the process of designing and evaluating a custom-made agent-based driving simulator for driver behaviour analysis. For the evaluation of the simulator an experiment was conducted with users to assess their driving style using a combination of a standardised driving style questionnaire and objective data from the simulator that described driving behaviour. During the experiment, objective and subjective information is obtained and analysed and a correlation is performed between actual and self-reported driving style. Results showed that participants exhibited a similar driving behaviour as in self reports and maintained an adequate level of situation awareness indicating realistic driving conditions.
Keywords: Agent-based development; Driver behaviour; Driving simulation; Virtual reality